New Approach to Effective Dry Grinding of Materials by Controlling Grinding Media Actions - Samat Baigereyev; Georgiy Guryanov; Ansagan Suleimenov; Boris Abdeyev (Applied Sciences)
The grinding process plays a crucial role in many technological operations. However, the complexity of increasing product fineness and energy efficiency in particle size reduction poses a problem in grinding processes. This study proposes a new approach for increasing grinding efficiency under dry grinding conditions in mills with grinding media. The approach involves a complex impact on the particle, in which it is subjected to two- and one-sided actions by the grinding media in the horizontal and vertical directions, respectively. The efficiency of the approach was tested by mathematical modeling and experimentation. The difference between the theoretical and experimental results was less than 11%, indicating the reliability of the proposed model. The results indicate that the proposed approach enhances the grinding efficiency by nearly fourfold and can be applied in industrial sectors that require high product fineness.